2007
DOI: 10.1017/s0266467407004427
|View full text |Cite
|
Sign up to set email alerts
|

Pollination ecology of Monstera obliqua (Araceae) in French Guiana

Abstract: Data on pollination ecology of Araceae are still scarce and most concern species belonging to the subfamily Aroideae (García-Robledo et al. 2004, Gibernau 2003, Ivancic et al. 2004, 2005; Maia & Schlindwein 2006). In this subfamily, inflorescences consist of unisexual flowers: female flowers are located in the lower portion and the male flowers are in the upper portion of the inflorescence (Mayo et al. 1997). In the documented neotropical Aroideae, pollinators are nocturnal beetles and pollination mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(41 citation statements)
references
References 18 publications
4
36
1
Order By: Relevance
“…2F), the unshed pollen would be amply protected by crystals. Consistent with the hypothesis that these crystals effectively protect gynoecia and stamens, predation on stamens or gynoecia by pollinating beetles was never observed in field observations, except for predation on stigmata of Montrichardia arborescens as described above (Ramírez and Gómez, 1978; Valerio, 1984; Young, 1986; Mayo et al, 1997; Gibernau et al, 1999, 2000, 2003; Maia and Schlindwein, 2006; Chouteau et al, 2007; Maia et al, 2010; Gibernau 2011). The constriction of the spathe to form a floral chamber might also help protect the anthers by discouraging the beetles from visiting them.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…2F), the unshed pollen would be amply protected by crystals. Consistent with the hypothesis that these crystals effectively protect gynoecia and stamens, predation on stamens or gynoecia by pollinating beetles was never observed in field observations, except for predation on stigmata of Montrichardia arborescens as described above (Ramírez and Gómez, 1978; Valerio, 1984; Young, 1986; Mayo et al, 1997; Gibernau et al, 1999, 2000, 2003; Maia and Schlindwein, 2006; Chouteau et al, 2007; Maia et al, 2010; Gibernau 2011). The constriction of the spathe to form a floral chamber might also help protect the anthers by discouraging the beetles from visiting them.…”
Section: Discussionsupporting
confidence: 71%
“…They share bisexual flowers and open spathes with the other bee‐pollinated species that we studied. However, it has been observed that, at least in some populations of Monstera obliqua , nitidulid beetles visit the inflorescence, pollinate the female flowers, and stay overnight in the lower part of the spathe (Chouteau et al, 2007), characteristics of a party‐house pollination strategy. The inflorescences lack sterile staminodia, but the beetles were observed to eat shed pollen (Chouteau et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Among thermogenic arums, the capacity for heat generation differs markedly, from approx. 1-2°C above ambient temperature in Monstera obliqua (Chouteau et al, 2007) to 34°C above in Philodendron bipinnatifidum (syn. Philodendron selloum; Nagy et al, 1972;Seymour et al, 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Chouteau et al . () show that the nitidulid pollinator Colopeterus amputatus uses inflorescences of Monstera obliqua as mating sites and feeds on the pollen during the staminate phase of anthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Amorphophallus, Cyrtosperma, Typhonium and Urospatha; Gibernau 2003; Punekar & Kumaran 2010) but information on their behaviour remains scarce. Chouteau et al (2007b) show that the nitidulid pollinator Colopeterus amputatus uses inflorescences of Monstera obliqua as mating sites and feeds on the pollen during the staminate phase of anthesis.…”
Section: Visitorsmentioning
confidence: 95%